Pengaruh Independensi, Keahlian Keuangan, Frekuensi Rapat, dan Masa Jabatan Komite Audit, Firm Size, serta Leverage terhadap Kecurangan Pelaporan Keuangan pada Perusahaan Industrials BEI Periode 2019–2024 - Noviyanti Dwi Wulandari; Dwi Soegiarto; Zaenal Afifi (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study investigates the influence of independent audit committees, audit committee financial expertise, meeting frequency, tenure, firm size, and leverage on financial reporting fraud. A quantitative research design is applied using secondary data derived from annual reports of industrial sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period, accessed through the official IDX website. The sample was selected using purposive sampling techniques and analyzed through logistic regression with SPSS version 31 to examine the relationship between independent variables and fraudulent financial reporting as the dependent variable. From 396 potential firm-year observations, 156 met the initial criteria, and after outlier elimination, 116 observations were included in the final dataset. The results reveal that audit committee independence, financial expertise, meeting frequency, tenure, firm size, and leverage do not significantly influence the occurrence of financial reporting fraud, indicating that these governance and firm characteristics may not effectively prevent fraudulent practices in reporting.